Bottle Trees, Bell, Queensland - Bain, Jack (1956)
Brachychiton rupestris, commonly known as the narrow-leaved bottle tree or Queensland bottle tree, is a tree in the family Malvaceae[a] native to Queensland, Australia. Discovered and described by Sir Thomas Mitchell and John Lindley in 1848, it gained its name from its bulbous trunk, which can be up to 3.5 metres (11 ft) diameter at breast height (DBH). Reaching 10–25 metres (33–82 ft) high, the Queensland bottle tree is deciduous, losing its leaves between September and December. The leaves are simple or divided, with one or more narrow leaf blades up to 11 centimetres (4 in) long and 2 centimetres (0.8 in) wide. Cream-coloured flowers appear from September to November, and are followed by woody boat-shaped follicles that ripen from November to May. No subspecies are recognised. (Wikipedia) Brachychiton rupestris (the Queensland Bottle Tree) are native to Queensland and are a unique and fascinating aspect of our state's natural heritage. The bottle-shaped trunk of the tree is created by the tree's ability to store water in its trunk during times of drought. The tree sheds its leaves during dry periods to conserve water, and the trunk swells with water storage to keep the tree alive. Bottle trees have been an important part of Queensland's heritage for centuries. First Nations people carved holes into the soft bark to use the water stored between the inner bark and the trunk. The seeds, roots, stems, and bark have all been used as a traditional source of food for people and animals. Today, bottle trees are protected by law in Queensland and can be found in parks, gardens, and other public areas in towns and cities across the state.